2007
DOI: 10.1186/1743-422x-4-48
|View full text |Cite
|
Sign up to set email alerts
|

Efficient replication of pneumonia virus of mice (PVM) in a mouse macrophage cell line

Abstract: Pneumonia virus of mice (PVM; family Paramyxoviridae, subfamily Pneumovirinae) is a natural respiratory pathogen of rodent species and an important new model for the study of severe viral bronchiolitis and pneumonia. However, despite high virus titers typically detected in infected mouse lung tissue in vivo, cell lines used routinely for virus propagation in vitro are not highly susceptible to PVM infection. We have evaluated several rodent and primate cell lines for susceptibility to PVM infection, and detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…In previous studies, we demonstrated that PVM replicates in mouse macrophage cell lines and also in primary peritoneal macrophages isolated from mice and challenged ex vivo (50,51). However, we demonstrate here for the first time that PVM infects both CD11c ϩ MHC-II ϩ DCs and CD11c ϩ Siglec-F ϩ AMs in vivo and that AMs support both active replication and production of infectious virions.…”
Section: Discussionsupporting
confidence: 47%
See 3 more Smart Citations
“…In previous studies, we demonstrated that PVM replicates in mouse macrophage cell lines and also in primary peritoneal macrophages isolated from mice and challenged ex vivo (50,51). However, we demonstrate here for the first time that PVM infects both CD11c ϩ MHC-II ϩ DCs and CD11c ϩ Siglec-F ϩ AMs in vivo and that AMs support both active replication and production of infectious virions.…”
Section: Discussionsupporting
confidence: 47%
“…Equal numbers of cells from all of the BAL fluid samples were plated. After 2 h, the nonadherent cells were removed and the adherent macrophages remaining were cultured for an additional 48 h. After 48 h, the culture supernatant was collected and dialyzed against 10 6 volumes of complete RPMI with 2% instead of 10% FBS across a 50-kDa membrane to remove low-molecular-weight cytokines prior to evaluation in a TCFD 50 assay as described in the next section. In some experiments, airway macrophages were isolated from mice that were control or L. plantarum primed as described above but not virus infected.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among these findings, several groups have detected immunoreactive eosinophil degranulation products in bronchial washings of patients with the most severe forms of RSV infection, 11,12 and we and others have reported direct recruitment of eosinophils to the lungs of PVM-infected mice. [13][14][15] RSV and PVM infections of their respective target cells result in the production of numerous proinflammatory cytokines, including the eosinophil chemoattractants RANTES and macrophage inflammatory protein-1␣/CCL3, [16][17][18][19] and RSV-infected target cells can activate eosinophils directly by virus-induced expression of ICAM-1. 20 Most intriguing, children who have recovered from severe RSV infection frequently go on to develop prolonged postinfectious wheezing 21 ; likewise, mice that have recovered from acute PVM infection experience persistent respiratory dysfunction with features similar to those described in mouse allergic asthma models.…”
Section: Introductionmentioning
confidence: 99%